2022
DOI: 10.1097/brs.0000000000004488
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Irisin on Human Nucleus Pulposus Cells: New Insights into the Biological Crosstalk between the Muscle and Intervertebral Disc

Abstract: Study Design. In vitro study. Objective. To investigate the effect of irisin on human nucleus pulposus cells (hNPCs) in vitro. Summary of Background Data. Physical exercise (PE) favours weight loss and ameliorates function in patients with low back pain. Although there is no biological evidence that the intervertebral disk (IVD) can respond to PE, recent studies have shown that running is associated with increased IVD hydration and hypertrophy. Irisin, a myokine released upon muscle contraction, has demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Indeed, both the addition of irisin to hTCs cultured in proinflammatory conditions and the later introduction of IL‐1β and TNF‐α in a hTC culture preconditioned with irisin resulted in an increase of mitochondrial activity and decrease of NO concentration, until reaching levels encountered with the standard medium alone. Altogether, these data suggest that irisin may protect hTCs from oxidative stress and blunt the detrimental effects of IL‐1β and TNF‐α in vitro, which have also been shown in other cell types 12,25,26 . Indeed, it has been recently reported that irisin enhanced mitochondrial membrane potential and ATP synthesis while attenuating IL‐1β‐mediated reactive oxygen species production, mitochondrial fusion, mitophagy, and autophagosome formation 27 .…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Indeed, both the addition of irisin to hTCs cultured in proinflammatory conditions and the later introduction of IL‐1β and TNF‐α in a hTC culture preconditioned with irisin resulted in an increase of mitochondrial activity and decrease of NO concentration, until reaching levels encountered with the standard medium alone. Altogether, these data suggest that irisin may protect hTCs from oxidative stress and blunt the detrimental effects of IL‐1β and TNF‐α in vitro, which have also been shown in other cell types 12,25,26 . Indeed, it has been recently reported that irisin enhanced mitochondrial membrane potential and ATP synthesis while attenuating IL‐1β‐mediated reactive oxygen species production, mitochondrial fusion, mitophagy, and autophagosome formation 27 .…”
Section: Discussionsupporting
confidence: 59%
“…Apart from its beneficial effects on several tissues, 9 the anabolic role of irisin has been recently elucidated in the musculoskeletal system 8 . Our group was the first to describe the effect of irisin on human articular chondrocytes 11 and nucleus pulposus cells 12 in vitro. In these studies, we found that such a myokine was able to increment cell proliferation, metabolism, and production of anabolic ECM markers while dampening the effect of in vitro inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hNPCs were isolated from IVD tissues of patients undergoing discectomy due to lumbar disc herniation ( n = 5, mean age = 57 ± 17 years old, Table 1 ) as previously described ( Vadalà et al, 2022 ). Tissue specimens were washed, annulus fibrosus and cartilaginous endplate tissues were carefully removed, and the NP tissue was minced and digested overnight in DMEM (Corning) with 1% P/S (Sigma), 5% FBS, and 0.01% collagenase type II (Worthington).…”
Section: Methodsmentioning
confidence: 99%